Efficacy of Single-Dose Primaquine With Artemisinin Combination Therapy on Plasmodium falciparum Gametocytes and Transmission: An Individual Patient Meta-Analysis. (11th August 2020) - Stepniewska, Kasia; Humphreys, Georgina S; Gonçalves, Bronner P; Craig, Elaine; Gosling, Roly; Guerin, Philippe J; Price, Ric N; Barnes, Karen I; Raman, Jaishree; Smit, Menno R; D'Alessandro, Umberto; Stone, Will J R; et al.
Abstract: Background: Since the World Health Organization recommended single low-dose (0.25 mg/kg) primaquine (PQ) in combination with artemisinin-based combination therapies (ACTs) in areas of low transmission or artemisinin-resistant Plasmodium falciparum, several single-site studies have been conducted to assess efficacy. Methods: An individual patient meta-analysis to assess gametocytocidal and transmission-blocking efficacy of PQ in combination with different ACTs was conducted. Random effects logistic regression was used to quantify PQ effect on (1) gametocyte carriage in the first 2 weeks post treatment; and (2) the probability of infecting at least 1 mosquito or of a mosquito becoming infected. Results: In 2574 participants from 14 studies, PQ reduced PCR-determined gametocyte carriage on days 7 and 14, most apparently in patients presenting with gametocytemia on day 0 (odds ratio [OR], 0.22; 95% confidence interval [CI], .17–.28 and OR, 0.12; 95% CI, .08–.16, respectively). Rate of decline in gametocyte carriage was faster when PQ was combined with artemether-lumefantrine (AL) compared to dihydroartemisinin-piperaquine (DP) ( P = .010 for day 7). Addition of 0.25 mg/kg PQ was associated with near complete prevention of transmission to mosquitoes. Conclusions: Transmission blocking is achieved with 0.25 mg/kg PQ. Gametocyte persistence and infectivity are lower when PQ is combined with AL compared to DP. Abstract : An individual patient meta-analysis was performed on the gametocytocidal and transmission-blocking activities of single-dose primaquine. Gametocyte persistence and infectivity depended on the artemisinin-combination therapy that primaquine was administered with. Primaquine's transmission-blocking effects were achieved at 0.25 mg/kg.